Optimizing composting process through mixture design for a sustainable valorization of residual biomass from medicinal and aromatic plants - Imane Mehdaoui; Zineb Majbar; El Mokhtar Saoudi Hassani; Rachid Mahmoud; Mohamed Ben Abbou; Loubna Bougarne; El Hassan Sakar; Mustapha Taleb; Zakia Rais; Fuad Khoshnaw (Environmental Research Communications)
Recently, medicinal and aromatic plants (MAP) gained a particular interest for their application in various fields such as food science, pharmacy, etc). MAP processing results in huge amounts of residual biomasses (RB). Such RB are valuable as they contain nutrients that can be recycled into high-value products rather than being considered waste. Composting emerges as a promising solution, effectively converting this biomass into a nutrient-rich product essential for plant growth. This research aimed to valorize RB from MAP through co-composting with green waste (GW) and poultry manure (PM) by optimising the initial mixture composition and evaluating the compost’s quality. A statistical mixture design approach was utilized to optimize the initial mixture composition. Sixteen of experiments were performed, focusing on pH and C/N ratio as response parameters. After monitoring the composting process, physicochemical parameters and the quality of the compost produced were evaluated. The results led to the successful development and validation of two response models using analysis of variance. The ideal mixture composition was found to be 45% RB-MAP, 25%PM, and 30% GW. The final compost exhibited a low C/N ratio, was rich in fertilizing and nutritive elements, and importantly, showed no phytotoxic effects. This research underscores the potential of composting as a sustainable method to convert RB into valuable agricultural resources.